Building fucoidan/agarose-based hydrogels as a platform for the development of therapeutic approaches against diabetes - Reys, Lara Priscila Lopes (2023)
Current management for diabetes has stimulated the development of versatile 3D-based hydrogels as in vitro platforms for insulin release and as support for the encapsulation of pancreatic cells and islets of Langerhans. This work aimed to create agarose/fucoidan hydrogels to encapsulate pancreatic cells as a potential biomaterial for diabetes therapeutics. The hydrogels were produced by combining fucoidan (Fu) and agarose (Aga), marine polysaccharides derived from the cell wall of brown and red seaweeds, respectively, and a thermal gelation process. The agarose/fucoidan (AgaFu) blended hydrogels were obtained by dissolving Aga in 3 or 5 wt % Fu aqueous solutions to obtain different proportions (4:10; 5:10, and 7:10 wt). The rheological tests on hydrogels revealed a non-Newtonian and viscoelastic behavior, while the characterization confirmed the presence of the two polymers in the structure of the hydrogels. In addition, the mechanical behavior showed that increasing Aga concentrations resulted in hydrogels with higher Youngâ s modulus. Further, the ability of the developed materials to sustain the viability of human pancreatic cells was assessed by encapsulation of the 1.1B4HP cell line for up to 7 days. The biological assessment of the hydrogels revealed that cultured pancreatic beta cells tended to self-organize and form pseudo-islets during the period studied.